2020
DOI: 10.14232/actacyb.285660
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Development of Iteration Procedures for the Interval-Based Simulation of Fractional-Order Systems

Abstract: In many fields of engineering as well as computational physics, it is necessary to describe dynamic phenomena which are characterized by an infinitely long horizon of past state values. This infinite horizon of past data then influences the evolution of future state trajectories. Such phenomena can be characterized effectively by means of fractional-order differential equations. In contrast to classical <em>linear</em> ordinary differential equations, <em>linear</em> fractional-order mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…As future work, we plan to extend the exponential enclosure technique to fractional-order differential equations by replacing the exponential terms with socalled Mittag-Leffler functions [23,24]. Fractional-order models have a large practical relevance in the context of control and state estimation of electrochemical energy converters and storage elements such as fuel cells and batteries.…”
Section: Discussionmentioning
confidence: 99%
“…As future work, we plan to extend the exponential enclosure technique to fractional-order differential equations by replacing the exponential terms with socalled Mittag-Leffler functions [23,24]. Fractional-order models have a large practical relevance in the context of control and state estimation of electrochemical energy converters and storage elements such as fuel cells and batteries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, further research should be directed towards extensions for arbitrarily fast changes of parameters occurring in a time-or event-triggered framework as well as to interfacing the proposed methodology with techniques for gain scheduling control of uncertain dynamic systems [33]. Moreover, possible generalizations towards the simulation of uncertain fractional-order differential equations will be investigated [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the parameters listed in the previous subsection, it can be shown that there does not exist a common, point-valued transformation matrix Θ according to Section 2.3 that simultaneously leads to a Metzler matrix representation for the transformed system dynamics stated in Equation (15) and at the same time preserves the asymptotic stability of the original system (46).…”
Section: Simulation-based Comparison Of Two Cooperativity-enforcing Similarity Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For further general discussions about modeling dynamic systems by using fractional-order representations, their identification, as well as their potential use in control engineering tasks, the reader is referred to [15]. Moreover, the paper [18] provides an overview of the state-of-the-art concerning already existing approaches for a verified simulation of fractional-order models. These include the definition of differential inclusions, the exploitation of cooperativity (i.e., monotonicity of solutions with respect to initial conditions) and positivity of state variables in simulation as well as state estimation, nonlinear time transformations to cast fractional-order models into equivalent integer-order representations, and, finally, also the extension of Picard iteration procedures [12] to non-integer-order models.…”
Section: Introductionmentioning
confidence: 99%